Monstresor's neurotic projections and paranoia in Edgar Allan Poe's “The Cask of Amontillado” - Lau, Zhe Ming; Wan Yahya, Wan Roselezam (International Institute for Science, Technology & Education, 2013)
Edgar Allen Poe, in his short stories, is well-known for his portrayal of strange behavior among his protagonists who usually commit a series of heinous crimes and either get away with it or are punished severely when discovered. In this paper, the actions of and thoughts spoken by Poe’s protagonist in his short story “The Cask of Amontillado” are interpreted in terms of the psychoanalytic concept of projection as articulated by Sigmund Freud. We believe projection is employed by Monstresor as an ego defense to exercise his aggressive drives of hatred and envy towards the victim, Fortunato, which culminates in premeditated murder. Fortunato is unaware of Monstresor’s plan to eliminate him permanently, while the reader is not informed about the unforgivable actions which have resulted in so much grievance and hatred in Monstresor’s mind, hence leaving the victim helpless and the reader baffled by Monstresor’s unjustified crime. By using Freud’s concept of projection, we conclude that the projective mechanism is a useful tool for understanding Monstresor’s motif in killing one of the social elite, Fortunato, and his actions in committing this gruesome crime. Monstresor is unconsciously projecting his own feelings of jealousy and arrogance onto Fortunato and imagining and believing that Fortunato has those same feelings towards him. So, obsessed with feelings of revenge, Monstresor takes the life of his innocent friend.